Developmental Psychology Perspectives on Consumer Book Choices in a Small-Scale Bookshop - Dilogini, S.; Kamshanaa, T.; Jayathissa, T.M.I.M.; Kumarasinghe, K.M.I.N.; Ranathunga, S.A.T.H.; Disanayake, W.G.S.U.; Bens, A.N.; Samarawickrama, L.G.P.K.; Subasinghe, N.S.; Danieal, M.; Kumari, S.M.V.H.T. (Faculty of Management Studies, Rajarata University of Sri Lanka, 2025)
From a developmental psychology perspective, this study explores how small-scale bookstores create a distinct developmental setting compared to libraries or online platforms. Unlike libraries, they combine learning with a shopping environment where decisions and purchasing behaviours mirror psychological needs across different life stages. Unlike online platforms, they offer face-to-face interactions, immediate access to resources and a sense of belonging within the community. In addition, these small-scale bookshops contribute to local economic growth while simultaneously acting as informal learning spaces that nurture intellectual, emotional and social development throughout the lifespan. The aim of this study is to explore how small-scale bookstores function as spaces for development, fostering intellectual curiosity, language skills, emotional well-being and social interaction to promote lifelong learning across different phases of human growth. Using a qualitative approach, data were collected through purposive sampling. Data saturation was achieved by triangulating these methods, such as six interviews, two focus group discussions with three staff members and customers, and systematic observations. The recurrence of similar insights across interviews and focus groups confirmed the adequacy of data and provided a well-rounded understanding of bookstore engagement. Thematic analysis revealed age-specific reading preferences: children gravitated toward picture books, adolescents relied on resource guides, adults preferred self-help and fiction, and older adults chose novels and political texts. These trends align with developmental psychology theories of cognitive, emotional and social growth, illustrating how bookstores adapt to changing needs across the life course. Ultimately, the study contributes theoretical insights into how developmental psychology can explain consumer book choices while offering practical implications for micro, small, and medium enterprises (MSMEs) to design bookshop environments that foster lifelong learning and strengthen community development.
Keywords: Developmental psychology; Emotional development; Learning resources; Local bookstores; Qualitative approach